Current Practices in the Management of Respiratory Virus Infections in Lung Transplantation: A European Survey of Clinical Practice. Issue 6 (June 2020) - Lhuillier, Elodie; Patout, Maxime; Marino, Philip; Arbane, Gill; Murphy, Patrick B.; Roux, Antoine; Thabut, Gabriel; Castier, Yves; Mal, Hervé; Brugiere, Olivier
Abstract : Supplemental Digital Content is available in the text.